Forest-stand structure and treeline dynamics of Himalayan Fir over the last four centuries in Kashmir, western Himalaya - Jain, Stuti; Chinthala, Bency David; Ranhotra, Parminder Singh; Pandey, Pushpendra; Shekhar, Mayank; Grießinger, Jussi; Joshi, Rajesh; Hamid, Maroof; Dar, Firdous A.; Shafee, Faizan; Khuroo, Anzar Ahmad; Singh, Chandra Prakash; et al. (Dendrochronologia, 2025)
The Himalaya supports a rich biodiversity and forest ecosystems providing important ecological services for a vast human population. Owing to the fragility of the Himalaya to environmental changes, precise knowledge about long-term forest functioning under warming-induced climate changes is crucial for future sustainability of forest resources. Treeline responses and changes in the forest-stand structure are indicators of ecosystem response to climate change. Using tree-ring data and tree size parameters, we investigated age-girth-height relationships by developing linear and nonlinear regression models, and calculated treeline shifts based on age-altitude relationships of Abies pindrow (Himalayan Fir) over the last four centuries from the Daksum-Sinthan (DK-SN) and Gulmarg (GUL) sites of Kashmir, western Himalaya. The Fir tree reached its upper elevation limit of >3500 masl by the mid-20th century, with average shift rates over 360 years of ∼1.42 and 1.79 m/yr at GUL and DK-SN, respectively. The recorded highest shift-rate of Fir occurred during the 17th century, coinciding with Little Ice Age climatic episode. Subsequent decline in shift-rates to <1 m/yr, relate to low-moisture conditions during the pre-monsoon months (April-June) hampering seedling establishment. Fir trees showed high recruitment rate during the 19th and 20th centuries at the study sites, as indicated by >50 % population of Fir trees younger than 200 years of age. Warming of spring season and availability of required soil-moisture probably helped to tree recruitment during last 200 years. The near stagnant upper limit of the Fir since last few decades at both sites hints towards the role of non-climatic factors including topography, land-surface-processes, and possibly anthropogenic activities. Our study provides crucial insights on the much-neglected long-term forest-stand dynamics and environmental changes in the treeline ecotone, with wide implications for biodiversity conservation and ecosystem restoration under the pressures of climatic and non-climatic factors.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Abies pindrow; Age-stand structure; Climate Change; Little Ice Age; Tree-rings; Treeline shift; Westerly Disturbances